Interleukin-6 "Trans-Signaling" and Ischemic Vascular Disease: The Important Role of Soluble gp130 - Mario Luca Morieri; Angelina Passaro; Giovanni Zuliani (Hindawi Limited, 2017)
Inflammation plays a major role in the onset of cardiovascular disease (CVD). Interleukine-6 (IL-6) is a multifunctional cytokine involved both in the beneficial acute inflammatory response and in the detrimental chronic low-grade systemic inflammation. Large genetic human studies, using Mendelian randomization approaches, have clearly showed that IL-6 pathway is causally involved in the onset of myocardial infarction. At the same time, IL-6 pathway is divided into two arms: classic signaling (effective in hepatocytes and leukocytes) and trans-signaling (with ubiquitous activity). Trans-signaling is known to be inhibited by the circulating soluble glycoprotein 130 (sgp130). In animal and in vitro models, trans-signaling inhibition with sgp130 antibody clearly shows a beneficial effect on inflammatory disease and atherosclerosis. Conversely, epidemiological data report inconsistent results between sgp130 levels and CV risk factors as well as CV outcome. We have reviewed the literature to understand the role of sgp130 and to find the evidence in favor of or against a possible clinical application of sgp130 treatment in the prevention of cardiovascular disease.